Desarrollo de una aplicación web progresiva PWA para la gestión y control de los servicios de atención médica en la clínica veterinaria “ZOOSALUD”. - Neto Chicaiza, Anderson Rodrigo (2023)
The "ZOOSALUD" Veterinary Clinic located in the central area of La Maná canton, province of Cotopaxi provides medical care services for all types of pets since 2003; the management and control of these services was carried out manually in such a way that it became a tedious process by having to consult some information required by the clients, which is why the proposal for the creation of a PWA Progressive Web Application arises applying the XP (Extreme Programming) methodology that consists of five phases which are planning, design, coding, testing and launch in a way that allows control in the scheduling of appointments and everything that is generated from it, as is the case of a record of clinical history, interns, inventory management among other processes that are involved, so that clients make the respective requests for medical appointments through the application and consult the information that requires conforming to the data entered of your pets. This was created with technologies such as JavaScript, CSS, PHP and React for the PWA part, supported the Bootstrap framework for the visual part, firmly confirming the requirements found in the initial phase obtained from research instruments such as surveys and Interview applied to the owner of the veterinary clinic.